Pengaruh Topografi dan Umur Ayam yang Berbeda terhadap Ketebalan Kerabang dan Ph Telur Ayam Ras Petelur - Wijaya, Andika Dony; Munir, Munir; Kadir, Muh. Jurhadi (Fakultas MIPA UNM, 2019)
Abstract. This study aims to determine the effect of topography and age of different breeds of chickens on egg weight and haugh unit. The study was conducted in August 2018, data collection was taken from Amparita Village, Tellu Limpoe District, Sidenreng Rappang Regency, Mario Village Kulo District, Sidenreng Rappang District and Kaluppang Village, Maiwa District, Enrekang District. The study used 135 eggs as eggs. The study used a Factorial Randomized Block Design with three stages of treatment and three repetitions, namely Factor A (Age of chicken 30 weeks, age of chicken 50 weeks, and age of chicken 70 weeks) then Factor B (Topography of lowland, medium and high). The treatment of topographic influence and age of laying chicken showed that the age of different chickens had no significant effect (P> 0.05) on eggshell thickness while the topography greatly affected eggshell thickness (P <0.01). Different age of race chicken has significant effect (P <0.05) on egg pH, and different topography has very significant effect (P <0.01) on egg ph.Keywords: Laying Chicken, Topography, Chicken Age, Shell Thickness and Egg pH